KAPABILITAS APARAT PEMERINTAH DAERAH DALAM MEMBERIKAN PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KELURAHAN GEMPOLSARI KOTA BANDUNG - Anika Anjani (Jurnal Caraka Prabu, 2018)
This research is motivated by a problem in the capability of local government officials in providing population administration services so that it needs to be further investigated. The research objective was to determine the extent of the improvement in the performance of the Gempolsari family officers in providing population administration services in Gempolsari Village, Bandung City. The research method used is descriptive research with a qualitative approach. The data is processed using data reduction, data categorization, synthesis, and formulation of working hypotheses as to the final step in the data compilation process. The results showed that the capability of Regional Government Officials in providing Population administration services in Gempolsari Village, Bandung City has not succeeded in increasing their performance as expected because the services provided by Government officials have not been optimal for applicants for demographic administration services.